Pengelolaan Tim dalam Event Organizer - Anton Tri Hasnanto (Journal on Education, 2025)
Team management in event organizers is a crucial aspect that influences the success of an event. This research aims to analyze strategies and best practices in team management, as well as their impact on the effectiveness and efficiency of organizing events. The methods used include surveys and interviews with event managers and team members in various organizations. The research results show that effective team management in event organizers is highly dependent on several key factors, including clear communication, appropriate division of tasks, and adequate training. A participative leadership style and good time management also play an important role in achieving event success. By identifying and overcoming existing challenges, event organizers can improve team performance and, ultimately, the quality of the events organized. These findings provide valuable insights for practitioners in this field to develop better team management strategies. Effective team management in event organizers greatly influences the success of the event. With a clear team structure, good communication, problem-solving skills, team member motivation, and a regular evaluation process, event organizers can improve their performance significantly. The investment in management time not only impacts the outcome of the event, but also on client satisfaction and the organization's reputation in the industry.